Atypical Anterior Tibial Stress Fracture Leading to Acute Fracture and Intermedullary Rodding - Emily Swisher; Chad Cochran; Raymond Duffett (Journal of Sports Medicine and Allied Health Sciences: Official Journal of the Ohio Athletic Trainers' Association)
OBJECTIVE This case highlights an unusual stress fracture progressing to an acute tibial fracture requiring intermedullary rodding.